A Lipid Transfer Protein Signaling Axis Exerts Dual Control of Cell-Cycle and Membrane Trafficking Systems - Huang, J.; Mousley, Carl; Dacquay, L.; Maitra, N.; Drin, G.; He, C.; Ridgway, N.; Tripathi, A.; Kennedy, M.; Kennedy, B.; Liu, W.; Baetz, K.; et al. (Cell Press, 2018)
© 2017 Elsevier Inc. Kes1/Osh4 is a member of the conserved, but functionally enigmatic, oxysterol binding protein-related protein (ORP) superfamily that inhibits phosphatidylinositol transfer protein (Sec14)-dependent membrane trafficking through the trans-Golgi (TGN)/endosomal network. We now report that Kes1, and select other ORPs, execute cell-cycle control activities as functionally non-redundant inhibitors of the G 1 /S transition when cells confront nutrient-poor environments and promote replicative aging. Kes1-dependent cell-cycle regulation requires the Greatwall/MASTL kinase ortholog Rim15, and is opposed by Sec14 activity in a mechanism independent of Kes1/Sec14 bulk membrane-trafficking functions. Moreover, the data identify Kes1 as a non-histone target for NuA4 through which this lysine acetyltransferase co-modulates membrane-trafficking and cell-cycle activities. We propose the Sec14/Kes1 lipid-exchange protein pair constitutes part of the mechanism for integrating TGN/endosomal lipid signaling with cell-cycle progression and hypothesize that ORPs define a family of stage-specific cell-cycle control factors that execute tumor-suppressor-like functions. Huang et al. demonstrate the yeast oxysterol-binding protein (ORP) homolog Kes1, and other ORPs, are inhibitors of the G 1 /S transition. They show that Kes1 is a non-histone target for the NuA4 lysine acetyltransferase and participates in a phosphatidylinositol-4-phopshate-dependent mechanism for integrating TGN/endosomal lipid signaling with cell-cycle progression.